Perspektif Etika Bisnis Islam Pada Sistem Konsinyasi Dalam Strategi Reseller - Fikri, Muhammad Khoirul (BISNIS, 2019)
The present study explores business behavior and consignment arrangements with suppliers demonstrated by Hamzah Batik, a batik and souvenir center in Yogyakarta,regarding the perspective of Islamic business ethics. A qualitative approach was employed in this field research. The data were collected through interviews with resellers, suppliers, and courier service and logistics companies dealing with Hamzah Batik as well as observation and documentation. The findings expose that Hamzah Batik performed positive business behavior concerning Islamic business ethics. It is worth noticing that the shopping centeremphasized visionary business leadership and managed a good consignment system with its suppliers. Additionally, both parties engaged in beneficial business cooperation. Hamzah Batik served the suppliers’ rights and obligations. This study promotes that corporate social responsibility and trust provided with suppliers constitute a very pivotal element in maintaining a successful business partnership.